EVALUASI SIMPANG TAK BERSINYAL DI SIMPANG LIMAU BUKITTINGGI - Bayu Kurniawan; Helga Yermadona; Surya Eka Priana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Simpang Limau is one of the Three Unsignalized Intersections on the Bukittinggi-Payakumbuh Cross Road, which has a fairly heavy traffic flow. The purpose of this study was to analyze the performance of an unsignaled intersection using MKJI 1997. The data needed in this study were primary data and secondary data. The primary data is in the form of data on traffic flow conditions, geometric intersections and environmental conditions. Secondary data includes population growth and road network maps. Traffic data collection is carried out by conducting a direct survey to the location for three days, namely Saturday, Sunday, and Monday from 07.00 to 18.00. This data was processed using Microsoft Excel based on the 1997 MKJI and the results obtained were made in the form of tables and graphs. From these tables and graphs it can be seen that the traffic volume, traffic composition, and peak hours that occur at the intersection. The results of calculations at peak hours with the highest flow, namely on Sundays at 17.00-18.00, the traffic volume at this intersection is 1,484 (pcu/hour). The traffic delay at the intersection is 3,066 (sec/pcu). The value of the degree of saturation in the existing condition of 0.74 does not exceed the MKJI determination of 0.75. The value of the intersection delay is 2.693 (sec/pcu) and the probability of the intersection queue is 22.32% to 71.68%.Key words : Unsignalized Intersection, Capacity (C), Degree of Saturation (DS), Delay (D), Probability of Queuing (QP%).